U.S. Physicians’ Views on E-Cigarette Risks and Benefits to Adults Who Smoke Versus Young People Who Do Not Smoke - Monica Magalhaes, PhD; Michelle T. Bover Manderski, PhD, MPH; Michelle Jeong, PhD; William J. Young, PhD; Michael B. Steinberg, MD, MPH; Nir Eyal, DPhil (AJPM Focus)
Introduction: Emerging evidence suggests that E-cigarettes are likely less harmful than combustible cigarettes, presenting an opportunity for adults who smoke to quit or switch. E-cigarettes also risk increasing the number of young people who become addicted to nicotine. Physicians’ perceptions of and attitudes toward this tradeoff remain underexplored. Methods: A random sample of U.S. physicians (N=940) were surveyed on a variety of tobacco-related issues and on their treatment practices and demographics. Questions aimed to elicit tradeoffs between protecting youth from becoming addicted to nicotine and helping adult smokers quit. Results: Most respondents (93%) reported caring about both helping adults quit smoking and protecting the young, with the majority (66.2%) prioritizing the latter. Of the various specialties, pediatricians were most likely to believe that preventing nicotine addiction among young people matters more than helping adults quit. Prioritization of youth over adults who smoke was also associated with being female, being younger, and having negative beliefs about the utility of E-cigarettes for smoking cessation. Conclusions: The findings show that physicians attribute greater ethical priority to protecting young people than to reducing risk to adults. Improved education on the risks versus benefits of E-cigarettes may assist physicians in making appropriate recommendations depending on patients' needs.